Control of Adipogenesis by the SUMO-Specific Protease SENP2 - Chung, Sung Soo (American Society for Microbiology (ASM), 2010)
Here, we demonstrate that SENP2, a desumoylating enzyme, plays a critical role in the control of adipogenesis. SENP2 expression was markedly increased upon the induction of adipocyte differentiation, and this increase was dependent on protein kinase A activation. Remarkably, knockdown of SENP2 led to a dramatic attenuation of adipogenesis with a marked decrease in PPARγ and C/EBPα mRNA levels. Knockdown of SENP2 also caused a marked reduction in the level of C/EBPβ protein but not in that of C/EBPβ mRNA. Interestingly, sumoylation of C/EBPβ dramatically increased its ubiquitination and destabilization, and this increase could be reversed by SENP2. In addition, overexpression of C/EBPβ could overcome the inhibitory effect of SENP2 knockdown on adipogenesis. Furthermore, SENP2 was absolutely required for adipogenesis of preadipocytes implanted into mice. These results establish a critical role for SENP2 in the regulation of adipogenesis by desumoylation and stabilization of C/EBPβ and in turn by promoting the expression of its downstream effectors, such as PPARγ and C/EBPα.